Gentamicin‐induced sensorineural auditory loss in healthy adult horses. (28th July 2021) - Aleman, Monica R.; True, Alexander; Scalco, Rebeca; Crowe, Chelsea M.; Costa, Lais R. R.; Chigerwe, Munashe
Abstract: Background: Irreversible sensorineural auditory loss has been reported in humans treated with aminoglycosides but not in horses. Objective: Investigate if auditory loss occurs in horses treated using the recommended IV daily dosage of gentamicin for 7 consecutive days. Animals: Ten healthy adult horses (7‐15 years; females and males, 5 each). Methods: Prospective study. Physical and neurological examinations and renal function tests were performed. Gentamicin sulfate was administered at a dosage of 6.6 mg/kg via the jugular vein on alternating sides for 7 days. Gentamicin peak and trough concentrations were measured. Horses were sedated using detomidine hydrochloride IV to perform brainstem auditory evoked responses (BAER) before the first dose, immediately after the last dose, and 30 days after the last dose. Peaks latencies, amplitudes, and amplitude ratios were recorded. Data from the second and last BAER were compared to results at baseline. Bone conduction was performed to rule out conduction disorders. Results: Seven horses had auditory loss: complete bilateral (N = 1), complete unilateral (N = 2), and partial unilateral (N = 4). Based on physical examination and BAER results, sensorineural auditory loss was suspected. Absent bone conduction ruled out a conduction disorder and further supported sensorineural auditory loss in horses with completely absent BAER. Auditory dysfunction was reversible in 4 of 7 horses. Conclusions and Clinical Importance: Gentamicin at recommended doses may cause sensorineural auditory loss in horses that might be irreversible. Follow‐up studies are needed to investigate if other dosing protocols present a similar risk.